Interleukin‐17 Inhibition in Spondyloarthritis Is Associated With Subclinical Gut Microbiome Perturbations and a Distinctive Interleukin‐25–Driven Intestinal Inflammation. Issue 4 (12th March 2020) - Manasson, Julia; Wallach, David S.; Guggino, Giuliana; Stapylton, Matthew; Badri, Michelle H.; Solomon, Gary; Reddy, Soumya M.; Coras, Roxana; Aksenov, Alexander A.; Jones, Drew R.; Girija, Parvathy V.; Neimann, Andrea L.; et al.
Abstract : Objective: To characterize the ecological effects of biologic therapies on the gut bacterial and fungal microbiome in psoriatic arthritis (PsA)/spondyloarthritis (SpA) patients. Methods: Fecal samples from PsA/SpA patients pre‐ and posttreatment with tumor necrosis factor inhibitors (TNFi; n = 15) or an anti–interleukin‐17A monoclonal antibody inhibitor (IL‐17i; n = 14) underwent sequencing (16S ribosomal RNA, internal transcribed spacer and shotgun metagenomics) and computational microbiome analysis. Fecal levels of fatty acid metabolites and cytokines/proteins implicated in PsA/SpA pathogenesis or intestinal inflammation were correlated with sequence data. Additionally, ileal biopsies obtained from SpA patients who developed clinically overt Crohn's disease (CD) after treatment with IL‐17i (n = 5) were analyzed for expression of IL‐23/Th17–related cytokines, IL‐25/IL‐17E–producing cells, and type 2 innate lymphoid cells (ILC2s). Results: There were significant shifts in abundance of specific taxa after treatment with IL‐17i compared to TNFi, particularly Clostridiales ( P = 0.016) and Candida albicans ( P = 0.041). These subclinical alterations correlated with changes in bacterial community co‐occurrence, metabolic pathways, IL‐23/Th17–related cytokines, and various fatty acids. Ileal biopsies showed that clinically overt CD was associated with expansion of IL‐25/IL‐17E–producing tuft cells and ILC2s ( P < 0.05), compared to pre–IL‐17i treatment levels. Conclusion: In a subgroup of SpA patients, the initiation of IL‐17A blockade correlated with features of subclinical gut inflammation and intestinal dysbiosis of certain bacterial and fungal taxa, most notably C albicans . Further, IL‐17i–related CD was associated with overexpression of IL‐25/IL‐17E–producing tuft cells and ILC2s. These results may help to explain the potential link between inhibition of a specific IL‐17 pathway and the (sub)clinical gut inflammation observed in SpA.